1998
DOI: 10.1038/sj.ejhg.5200170
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-genotype correlation in Jewish patients suffering from familial Mediterranean fever (FMF)

Abstract: Familial Mediterranean Fever is one of the most frequent recessive disease in non-Ashkenazi Jews. The gene responsible for the disease (MEFV) has very recently been identified. The M694V ('MED') mutation was found in about 80% of the FMF Jewish (Iraqi and North African) chromosomes. To see if the presence of this mutation could be correlated with particular traits of the disease, we examined a number of clinical features in a panel of 109 Jewish FMF patients with 0, 1 or 2 MED mutations. We showed that homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
6
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 1 publication
(1 reference statement)
8
98
6
4
Order By: Relevance
“…In our study population there were no significant differences in the clinical presentation of FMF patients carrying different mutations, although both Pras et al 20 and Dewalle et al 17 found that homozygosity for the Met694Val mutation was significantly associated with a more severe form of the disease. A possible explanation could be that the NAJ patients have a phenotype which is different from that of other ethnic groups, even when they have the same genotype.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…In our study population there were no significant differences in the clinical presentation of FMF patients carrying different mutations, although both Pras et al 20 and Dewalle et al 17 found that homozygosity for the Met694Val mutation was significantly associated with a more severe form of the disease. A possible explanation could be that the NAJ patients have a phenotype which is different from that of other ethnic groups, even when they have the same genotype.…”
Section: Discussioncontrasting
confidence: 44%
“…Yalçinkaya et al 18 reported two patients with amyloidosis who were both compound heterozygotes Val726Ala/Met680Ile, and Dewalle et al 17 reported an Arab kindred where all the affected individuals were homozygotes for Met694Ile. The third case, reported by Pras,19 was one patient with systemic amyloidosis who was homozygous for Val726Ala.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the isolation of the MEFV gene and mutations, numerous studies tested the genotype-phenotype correlations in FMF patients in different countries. When FMF was first discovered, it was shown that homozygosity for p.M694V was associated with more severe disease, including early onset, more frequent attacks, significantly more joint disease, a higher dose of colchicine needed to control attacks, and a higher rate of amyloidosis among patients not adequately treated (28). These results were confirmed in further studies performed in Israel, France (with Armenian patients), and in Middle Eastern countries (Jordan and Lebanon) (22)(23)(24).…”
Section: Clinical Manifestations Of Fmf In Various Populationsmentioning
confidence: 99%
“…We thus investigated the impact of the most common FMFassociated genotype, M694V/M694V, which is known to be correlated with a severe disease course. [21][22][23] We observed no significant difference in cytokine mRNA levels between M694V/M694V patients and other FMF patients with a different genotype (Figure 2b).…”
mentioning
confidence: 99%